JAVA IN PUMA (POP UP MAP) - Soedarmodjo, Theo Prastomo (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Indonesia is a country rich islands cultural diversity. This leads to a lot of other nations came to Indonesia to enjoy the beauty of Indonesian culture and learning. But the Indonesian people themselves are less familiar with their own culture so much territory and national culture in claims by other nations. Therefore we aim to provide knowledge about the area and culture through the medium of JAVA IN PUMA (POP UP MAP) with a fun simulation method to produce a generation that knows the area and understands his homeland in the uniqueness of its culture.